'A Library is a Growing Organism': Redefining Artificial Intelligence and the Role of the Information Professional in the Corporate Legal World. (June 2022) - Hearn, Jake
Abstract: This article, written by Jake Hearn, seeks to define and reevaluate artificial intelligence (AI) in the context of the corporate legal world. The article explores some of the opportunities on offer to information professionals to ensure that the profession continues to grow within the economic, cultural and professional context it is situated.